L-Carnitine supplementation increases expression of PPAR-? and glucose transporters in skeletal muscle of chronically and acutely exercised rats - Pala, Ragip; Genc, Eyup; Tuzcu, Mehmet; Orhan, Cemal; Şahin, Nurhan; Er, Besir; Şahin, Kazım (C M B Assoc, 2018)
In this study, the effects of L-Carnitine supplementation on the lipid peroxidation and expression of PPAR-gamma and glucose transporters in the liver and muscles of chronically and acutely exercised rats were investigated. A total of 42 male Wistar Albino rats (8-week-old) were divided into six groups as follows: Control, L-Carnitine, Chronic Exercise (CE), Chronic Exercise + L-Carnitine, Acute Exercise (AE) and L-Carnitine + Acute Exercise. Chronic exercise consists of 30 m/min, 30 min/day, and 5 days/week for 6 weeks. Rats in the acute exercise groups were run on the treadmill at 30 m/min until exhaustion. L-Carnitine was given at the level of 300 mg per kilogram of diet for 6 weeks. There was no significant difference in the levels of serum ALT, AST, urea, creatinine and glucose levels between the exercise and L-Carnitine groups (P > 0.05). Cholesterol and triglyceride levels decreased by L-carnitine supplementation and chronic exercise in control groups but increased in the AE groups compared to the control group without reinforcement (P < 0.05). Serum, muscle, heart, and liver malondialdehyde (MDA) concentrations were lower in CE and higher in the AE groups (P < 0.001). However, L-Carnitine supplementation reduced MDA levels (P < 0.05). Liver and muscle PPAR-gamma, liver GLUT-2 and muscle GLUT-4 mRNA expressions were lower in AE group than in all other groups (P < 0.001). Both chronic exercise and supplemental L-Carnitine increased liver and muscle PPAR-gamma, GLUT-2 and GLUT-4 mRNA expression (P < 0.05). As a result, although acute exercise increased oxidative stress, chronic exercise reduced oxidative stress by lowering lipid peroxidation level. L-Carnitine supplementation decreased oxidative stress and improved glucose and lipid metabolism by regulation of PPAR-gamma, GLUT-2 and GLUT-4 mRNA expression in rats.
Keywords: L-Carnitine; Exercise; Oxidative stress; PPAR-gamma; Glucose transporters